"It's better than nothing, but I do not find it to be ideal": Older adults' experience of TeleRehab during the first COVID-19 lockdown. (May 2023) - Rotenberg, Shlomit; Oreper, Julie S.; Bar, Yael; Davids-Brumer, Naomi; Dawson, Deirdre R.
This qualitative study used descriptive thematic analysis to explore the experiences of 16 older adults (age: 71 ± 6.4) who transitioned from an in-person to telerehabilitation (TeleRehab) group intervention in March 2020. We found the following themes: (1A) Technology Use, describing challenges and need for support; and (1B) Technology Self-Efficacy, describing how technological ability was attributed to past-experience and/or age. Four themes described the intervention experience. First, "Not The Same, But Better Than Nothing" (2A), reflected a preference for in-person intervention. Specifically, in-person training provided a better social experience (theme 2B), and stronger accountability, although the content was well delivered in both modalities (theme 2C). Contextual factors (theme 2D) that played a role were ease of commute, especially important during the winter, and the context of the lockdown, that positioned the TeleRehab intervention as a meaningful social activity. However, sensory impairments, and/or distractions in the home diminished the TeleRehab experience.